2019
DOI: 10.2478/jomb-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selected CD45+ cell subsets’ response and cytokine levels on exhaustive effort among soccer players

Abstract: SummaryBackgroundImmunological alterations may led to the reduction in capacity and endurance levels in elite athletes by e.g. increased susceptibility to infections. There is a need to explain the impact of intensive physical effort on the CD4+memory T cell subsets.MethodsFourteen participants median aged 19 years old (range 17–21 years) were recruited form Pogoń Szczecin S.A., soccer club. They performed progressive efficiency test on mechanical treadmill until exhaustion twice: during preparatory phases to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 27 publications
(51 reference statements)
6
28
3
Order By: Relevance
“…Moreover, exercise of high and very high intensity increases the risk of upper respiratory tract infections in contrast to regular moderate intensity physical activity [36,42,44,45]. Our previous study showed that Th cells play an important role in regulation and modulation of the immune response to progressive effort until exhaustion performed on a mechanical treadmill [20,35]. The present study confirms that the immune response induced by the progressive effort is associated with the Th1 but not Th2 cell subset.…”
Section: Th Cell Subset Alterationssupporting
confidence: 83%
See 3 more Smart Citations
“…Moreover, exercise of high and very high intensity increases the risk of upper respiratory tract infections in contrast to regular moderate intensity physical activity [36,42,44,45]. Our previous study showed that Th cells play an important role in regulation and modulation of the immune response to progressive effort until exhaustion performed on a mechanical treadmill [20,35]. The present study confirms that the immune response induced by the progressive effort is associated with the Th1 but not Th2 cell subset.…”
Section: Th Cell Subset Alterationssupporting
confidence: 83%
“…On the other hand, an increase in IL-4 levels observed only in the Beep group suggests more rapid pro-inflammatory response even though there were no significant increases in the percentage of Th2 cells. As was found in our previous study, NK cells are the most intensively recruited immediately after the endurance effort [35]. The role of posteffort responses related to NK cells may explain this phenomenon.…”
Section: Post-effort Cytokine Releasesupporting
confidence: 77%
See 2 more Smart Citations
“…Taking the fact that WBC parameters (count and percentages of total WBC and their subpopulations) are the markers of general health status into account, the observed results of the present study may be considered as positive and confirming properly prescribed training loads and organism's adaptation to them. Our previous works revealed post-effort increase in WBC parameter values caused not so much by the dehydration but related to immunological response to performed exercise [58][59][60].…”
Section: The Impact Of the Training Program On Red And White Blood Cementioning
confidence: 94%